Trends of Hepatitis B and Hepatitis C Mortality in Canada, 1979–1997 - Pohani, Gina (Can J Public Health, 2001)
Mortality data from Statistics Canada were analyzed to measure the temporal trends and burden of illness attributed to viral hepatitis in Canada. Analysis of age-standardized mortality rates from 1979 to 1997 showed an increasing trend in mortality for both hepatitis B and non-A, non-B hepatitis (NANBH), most of which are attributed to hepatitis C infections. Hepatitis B and NANBH agestandardized mortality rates increased respectively, from 0.03 and 0.12 deaths per 100,000 population in 1979 to 0.26 and 0.41 deaths per 100,000 in 1997. Male mortality rates were consistently higher than female for both diseases. Among deaths from chronic liver disease, over 1,000 deaths were estimated to have been caused by hepatitis B and hepatitis C annually. Although the hepatitis B or NANBH recorded deaths largely underestimate the true burden of HBV and HCV in Canada, the temporal trends are useful as they reflect changes in the impact of both diseases.